2016
DOI: 10.1108/ijphm-02-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of hospital brand image and the relationships with medical tourists’ behavioral intention

Abstract: Purpose Medical tourism is growing rapidly in the recent years in various Asian countries. The success of the hospitals engaged in medical tourism largely depends on their abilities in maintaining the repeating customers and to attract new customers. Hence, the purpose of this study is to examine the impacts of word-of-mouth and social media on hospital brand image. It also attempts to examine the relationships between brand image, perceived service quality, patient satisfaction and behavioral intention. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
85
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(97 citation statements)
references
References 67 publications
(58 reference statements)
9
85
3
Order By: Relevance
“…Specifically, it is necessary to pay attention to creating a good social environment to enhance the emotional image that matches the self-image of tourists (H. Zhang, 2018). Meanwhile, the result shows that WOM is an important predictor of tourists' behavioral intentions, which is consistent with previous studies (Cham et al, 2016;Hossain & Kim, 2018;Jalilvand et al, 2013). This means that WOM behavior has an important impact on premium behavior and willingness to revisit, which suggests that incentive WOM marketing should be employed to promote tourists' willingness to revisit.…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, it is necessary to pay attention to creating a good social environment to enhance the emotional image that matches the self-image of tourists (H. Zhang, 2018). Meanwhile, the result shows that WOM is an important predictor of tourists' behavioral intentions, which is consistent with previous studies (Cham et al, 2016;Hossain & Kim, 2018;Jalilvand et al, 2013). This means that WOM behavior has an important impact on premium behavior and willingness to revisit, which suggests that incentive WOM marketing should be employed to promote tourists' willingness to revisit.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, Pan and Chen (2014) found that satisfaction of medical tourists was driven by the following four factors: (1) advanced equipment of a medical institution, (2) professional and skillful technicians, (3) professional and reliable physicians, and (4) the hospital medical quality. Jaapar et al (2017) corroborated the quality–satisfaction relationship in a specific medical tourism context, that is, dental tourism, while Cham et al (2016) obtained the same results in a study of hospital brands.…”
Section: Literature Reviewsupporting
confidence: 59%
“…In fact, patient satisfaction has been considered in the same terms as customer satisfaction (Rad et al, 2010) and can be defined as the extent to which patients’ expectations are met by the health-care service providers (Debono & Travaglia, 2009). Accordingly, several studies from the medical tourism literature focused on customer satisfaction, expectations, and/or perceived quality of different medical tourism services provided by health-care facilities, such as hospitals and medical clinics (e.g., Cham et al, 2014; Cham et al, 2016; Chou et al, 2012; Guiry et al, 2013; Guiry & Vequist, 2011; Han & Hyun, 2015; Jaapar et al, 2017; Lertwannawit & Gulid, 2011; Prajitmutita et al, 2016; Rad et al, 2010; Wang, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Product trust was measured with three items adapted from Choe et al's scale [106]. Word of mouth is measured with five items developed by Cham et al's scale [107].…”
Section: Methodsmentioning
confidence: 99%